Governance in cross-border metropolitan regions. The case of Greater Copenhagen - Danielewicz, Justyna (Współrządzenie w transgranicznych regionach metropolitalnych na przykładzie Wielkiej Kopenhagi, 2020)
Cross-border cooperation in Europe has intensified in recent years. Organizations with varying institutional characteristics have emerged in urban areas that cross national borders to address the issues of the cross-border situation. This article sets out to analyse the collaboration in metropolitan region of Greater Copenhagen. The research review method was used in the literature review of cross-border regions and governance, and the descriptive-analytical research method was employed to explore the governance system of the metropolitan region of Greater Copenhagen. The research method was based on the analysis of secondary data and the related formal documents on Greater Copenhagen’s government system. The analysis showed that the regional collaboration among different actors is a well-established practice. The concept of multi-level governance is implemented in Greater Copenhagen and brings measurable effects, but there are still barriers and new challenges to deeper integration
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 2, s. 135-145
Keywords: cross-border region; multi-level governance; cooperation; Greater Copenhagen; metropolitan areas; regiony transgraniczne; współrządzenie wielopoziomowe; współpraca; Wielka Kopenhaga; obszary metropolitalne